Analisis Pengaruh Kompetensi Terhadap Kinerja Karyawan Badan Pengelola Dan Pengembangan Taman Mini Indonesia Indah - Zakiyah, Zakiyah (Universitas PGRI Yogyakarta, 2016)
Taman Mini Indonesia Indah (TMII) is the second largest tourist destination in Jakarta. Until now TMII is managed by the Management Board and Development Taman Mini Indonesia Indah (TMII BPP). The number of employees BPP TMII, early out by 2015, as many as 734 people. In the period 2011-2014, employees performance BPP TMII yet optimal and showed the phenomenon tends to decrease. Similarly, the level of competency of the employees pointed to the fact remains low ordo not meet minimum standards set BPP TMII management, among others, by 78.75% of the employees had high school education or less. The issue is whether the employees competence affect the performance? with reference to the formulation of the problem, the study aims to examine and analyze whether BPP TMII employees competence variable effect on performance. The study design used is associative research. The study population was all employees assigned BPP TMII. Because of the size of the population is large, this study used a sample. The minimum sample size is determined by the formula Slovin and with a level of fault tolerance selected by 5%, then obtained a sample size of 259 people. The sampling method used simple random sampling. Furthermore, the research hypothesis was tested using statistical models of linear regression and multiple linear regression. The test results prove the hypothesis that the variables of competence by dimensional motif, character, selfconfidence, knowledge, skills, either partially or simultaneously have a significant positive effect on employees performance BPP TMII, and the coefficient of determination obtained 52.7%